Redesigning the Indian Food Security System through E-Governance: The Case of Kerala - SILVIA MASIERO (World Development, 2015)
The link between e-governance and development has been widely leveraged for policy formulation in India, however, little is known about its application to food security. This paper fills the gap with a study of Kerala, where the Public Distribution System (PDS), the main national food security program, has been digitalized in its main functions. Findings reveal that the digital program has been purposefully devised to combat the problem of diversion (“rice mafia”) of PDS goods to the market: however, issues of partial coverage and mistargeting remain. Lessons are drawn for other states computerizing the PDS and their social safety nets. 2014 Elsevier Ltd. All rights reserved.